The FlgT Protein Is Involved in Aeromonas hydrophila Polar Flagella Stability and Not Affects Anchorage of Lateral Flagella - Merino, Susana; Tomás, Juan M. (Frontiers in Microbiology, 2016)
Aeromonas hydrophila sodium-driven polar flagellum has a complex stator-motor. Consist of two sets of redundant and non-exchangeable proteins (PomA/PomB and PomA2/PomB2), which are homologous to other sodium-conducting polar flagellum stator motors; and also two essential proteins (MotX and MotY), that they interact with one of those two redundant pairs of proteins and form the T-ring. In this work, we described an essential protein for polar flagellum stability and rotation which is orthologous to Vibrio spp. FlgT and it is encoded outside of the A. hydrophila polar flagellum regions. The flgT was present in all mesophilic Aeromonas strains tested and also in the non-motile Aeromonas salmonicida. The A. hydrophila ∆flgT mutant is able to assemble the polar flagellum but is more unstable and released into the culture supernatant from the cell upon completion assembly. Presence of FlgT in purified polar hook-basal bodies (HBB) of wild-type strain was confirmed by Western blotting and electron microscopy observations showed an outer ring of the T-ring (H-ring) which is not present in the ∆flgT mutant. Anchoring and motility of proton-driven lateral flagella was not affected in the ∆flgT mutant and specific antibodies did not detect FlgT in purified lateral HBB of wild type strain.